Legal Mechanisms in Handling Work Relationship Tensions in Modern Organizational Environments - Khayru, Rafadi Khan (Journal of Social Science Studies, 2024)
Employment law holds an important position in maintaining balanced employment relations and minimizing the potential for conflict within organizational environments. This study aims to examine the extent to which legal mechanisms are able to regulate and resolve workplace conflicts effectively within the realities of modern organizations. The research adopts a literature study approach by reviewing relevant academic sources to analyze the dynamics of power imbalances between employers and employees, institutional weaknesses, and the limited legal culture that often affects the process of resolving labor disputes. The findings indicate that employment law frequently fails to perform its corrective and protective functions due to several barriers, including weak implementation, limited access to justice, and a significant gap between formal legal norms and practical realities in the workplace. In many cases, workers face structural constraints that hinder them from utilizing available legal mechanisms effectively. Furthermore, the study reveals that the role of law should not remain merely reactive in addressing disputes after conflicts arise. Instead, it needs to shift toward a more preventive and reconciliatory approach through institutional transformation, stronger enforcement mechanisms, and increased legal awareness among both employers and employees. By strengthening these aspects, employment law can function more effectively in maintaining fair work relations and reducing organizational conflict. This study contributes a conceptual perspective to the development of a more adaptive and responsive conflict resolution system in the context of evolving global work structures.